Deserts - Ganeri, Anita (Milwaukee, WI Gareth Stevens Publishing, 2003)
Describes the characteristics of different types of deserts around the world, the plants and animals that inhabit them, and the various issues that will affect the future of these areas.
Keywords: Deserts; Desert ecology; Ecology